Characteristics of carotenoids and their use in the cosmetics industry - Baran, Marzena Teresa; Miziak, Paulina; Bonio, Katarzyna (Journal of Education, Health and Sport, 2020)
Carotenoids are compounds of natural origin and are a product of secondary metabolism of plants and bacteria. These are chemically unsaturated hydrocarbons that act as dyes with a wide range of colors. These compounds are stored in chloroplasts and chromatophores. In living organisms, they are used in the photosynthesis process, have a protective function in the photooxidation process and are designed to neutralize free radicals. Due to the difference in structure, the molecules were divided into 2 groups, i.e. orange - carotenes and yellow - xanthophylls. Due to their unique antioxidant properties, they are widely used in the cosmetics industry. Carotenoids as antioxidants have a beneficial effect on human health and well-being. Currently, the most popular compounds that are used in cosmetology are carotene and lycopene. The development of cosmetology followed the development of biochemistry, chemistry, pharmacy and medicine. Compounds used in care products can be obtained as extracts from plants or obtained by chemical synthesis or biotechnological processes. It can be seen that in recent years the awareness of the use of cosmetic products has increased. This contributed to the increased interest in cosmetics of natural origin. Thanks to the interest in natural / ecological products, we have the opportunity to get to know biologically active substances better and to fully use them in cosmetology, pharmacology and medicine.